MENINGKATKAN PROFESIONAL GURU DALAM PEMBUATAN ADMINISTRASI MELALUI SUPERVISI AKADEMIK KEPALA SEKOLAH SD NEGERI REJOSARI 03 KOTA SEMARANG - Rahayu, Seger Sri (Persatuan Guru Republik Indonesia Kota Semarang, 2022)
The weakness of teachers in making their respective administrations is weak, the decline in morale greatly affects teacher professionals, especially learning administration. The facts show that teachers are still weak professionally and performance is declining. Efforts made to overcome the problems mentioned above are to carry out academic supervision carried out by the principal by carrying out direct or indirect coaching. The results after being carried out with the principal's academic supervision obtained changes in the performance and professional improvement of teachers, especially in learning administration at SD Negeri Rejosari 03. Significant results were obtained that there was a change in performance in teacher professional improvement from 60% to 80%. The impact of the implementation of the principal's academic supervision is: (1) developing the expertise of teachers in their respective fields. (2) increased work ethic. (3) the attitude of independence begins to appear In the implementation of this research, there are several obstacles in the principal's academic supervision, namely the teacher administration still has shortcomings both systematically and from the amount specified. Cohesiveness and the spirit of cooperation can help in research on teacher professional improvement in making administration through the academic supervision of the principal. Based on the results of this study, it is recommended that principals and teachers can try more varied supervision techniques so that the professionalism of teachers can improve better and maintain and improve teacher development models by guiding teachers in improving professionalism.